2022
DOI: 10.1038/s41423-022-00926-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor extracellular vesicles mediate anti-PD-L1 therapy resistance by decoying anti-PD-L1

Abstract: PD-L1+ tumor-derived extracellular vesicles (TEVs) cause systemic immunosuppression and possibly resistance to anti-PD-L1 antibody (αPD-L1) blockade. However, whether and how PD-L1+ TEVs mediate αPD-L1 therapy resistance is unknown. Here, we show that PD-L1+ TEVs substantially decoy αPD-L1 and that TEV-bound αPD-L1 is more rapidly cleared by macrophages, causing insufficient blockade of tumor PD-L1 and subsequent αPD-L1 therapy resistance. Inhibition of endogenous production of TEVs by Rab27a or Coro1a knockou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…However, knockout of PDL1 or administration of blocking antibodies systemically may cause systemic complications, which could further affect blood pressure, as evidenced by the fact that both hypotension and hypertension are observed as side effects in cancer patients treated with PDL1 inhibiting antibodies. [51][52][53][54][55][56] Therefore, we employed renal tubule specific nanoparticles [33][34][35] to introduce siRNAs designed to specifically knockdown PDL1 in renal tubules. Kidney-targeted polymeric mesoscale nanoparticles containing siPDL1 were injected intravenously into mice via tail vein 1 day after the start of DOCA-salt treatment.…”
Section: Renal Tubule Specific Knockdown Of Pdl1 Ameliorates T-cell A...mentioning
confidence: 99%
“…However, knockout of PDL1 or administration of blocking antibodies systemically may cause systemic complications, which could further affect blood pressure, as evidenced by the fact that both hypotension and hypertension are observed as side effects in cancer patients treated with PDL1 inhibiting antibodies. [51][52][53][54][55][56] Therefore, we employed renal tubule specific nanoparticles [33][34][35] to introduce siRNAs designed to specifically knockdown PDL1 in renal tubules. Kidney-targeted polymeric mesoscale nanoparticles containing siPDL1 were injected intravenously into mice via tail vein 1 day after the start of DOCA-salt treatment.…”
Section: Renal Tubule Specific Knockdown Of Pdl1 Ameliorates T-cell A...mentioning
confidence: 99%
“…Besides, some tumors develop resistance to immunotherapy despite being sensitive at start 33,34 . Chen et al found that exosomal PD‐L1 acted as decoy and bount to anti‐PD‐L1, which was then subsequently cleared more quickly by macrophages, resulting in anti‐PD‐L1 therapy resistance 17 . In addition, high levels of circulating exosomal PD‐L1 may indicate that the patient's T cells are depleted and anti‐PD‐1 therapy will fail 35 .…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that PD‐L1 relies on direct contact between tumor cells and immune cells to exert its function. However, emerging evidence suggests that prostate cancer cells can suppress the function of T cells in draining lymph nodes or block anti‐PD‐L1 antibodies by secreting exosomal PD‐L1 into the system 16,17 . Thus, exosomal PD‐L1 is critical for resistance to anti‐PD‐L1 immunotherapy in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[43] On the one hand, exoPD-L1 is secreted to distal tissues by cancer cells, [38] and then attaches to PD-1 on the surface of T cells, which in turn suppresses and tyrannizes the immune system. [40,44] On the other hand, exoPD-L1 is found to effectively impede the activation and proliferation of T cells, and then exhibit a certain against anti-PD-L1 antibody blockade to some extent, [45] which can be reversed through the administration of anti-PD-1 treatment in glioblastoma and various other cancer types. [46] In addition to suppressing T cell functions, exoPD-L1 may act on the polarization of macrophages.…”
Section: The Structure and Function Of Extracellular Pd-l1mentioning
confidence: 99%